Predicting death in children. Issue 12 (18th June 2008) - Brook, L; Hain, R
Abstract : Rarely do paediatric palliative medicine physicians have to break the news of a diagnosis of a life-limiting condition. It is much commoner for us to be faced with the question: "how long?". This cannot be answered with certainty, and yet a great deal may depend on it. While palliative care should ideally be available from diagnosis, the need for "active" practical palliative care intervention will fluctuate during the course of a child's illness, often over months or years, sometimes decades. Typically, there will be several periods during which death seems likely before the final terminal episode, particularly among children with non-malignant life-limiting condition. Optimal management of all episodes depends on anticipating the child's needs, which in turn depends on recognising that such an episode has begun. Providing adequate palliative care critically depends on making a diagnosis of dying. In this article, we will consider why it is important to make a diagnosis of dying, briefly review some of the helpful tools available, and examine some of the evidence from published literature in children and adults.